This is the truth - Sheikh Abdul Majid Azzindani..; Muslim World League. Mecca (Mecca : produced by Commission on Scientific Signs of the Qur'an and Sunna, 1900)
The video features interviews between Sheikh Azzindani and Scientists from all over the world demonstrating the marvels of the Quran. Many of the scientists are non-Muslims
Backup available in VHS 1/2 in.
Copy available in DVD format
Keywords: Islam and science